Determine and compare the viewpoints of nurses, patients and their relatives to workplace violence against nurses. (23rd March 2018) - Babaei, Nasib; Rahmani, Azad; Avazeh, Marziyeh; Mohajjelaghdam, Ali‐Reza; Zamanzadeh, Vahid; Dadashzadeh, Abbass
Abstract : Aim: The present study aims to assess the perception of nurses, patients and their relatives regarding the nature of workplace violence against nurses. Background: Workplace violence adversely affects the health, well‐being and safety of nurses and the quality of nursing care. Methods: In the present descriptive comparative study, the nature of violence was assessed using a modified and validated International Labor Office, the International Council of Nurses, World Health Organization, and Public Services International Questionnaire. Results: Nurses, patients and relatives reported verbal abuse as the most common and sexual violence as the least common type of violence against nurses. Nurses mostly blamed factors associated with patients and their relatives as the cause of violence, whereas patients and their relatives blamed social factors. Conclusions: This study shows that violence is significantly prevalent in clinical settings, but its nature is differently perceived by nurses, patients and their relatives. This phenomenon requires further studies because knowledge of the causes of this difference could help to reduce and control violence. Implications for Nursing Management: It is necessary that nursing managers inform nurses about protocols for reporting all such cases in order to collect information, and based on a clear procedure, actively pursue reported cases and take the necessary measures to prevent violence against nurses.